Tantangan Wirausaha Penjual Kuliner Tradisional di Tengah Popularitas Makanan Modern Era Globalisasi Saat Ini : (Studi Kasus Usaha Lemang dan Tape Desa Karang Rejo) - Malvira Pohan; Natasia Theofani Margaret; Sernanda Putri Darma (Jurnal Ilmiah Ekonomi, Akuntansi, dan Pajak, 2024)
This research aims to analyze how traditional culinary MSMEs in Karang Rejo Village, Langkat Regency, adapt to global and digital competition. The focus is on the production and marketing strategy of sweet potato tape, pulut tape and lemang. This qualitative research uses in-depth interview methods with MSME owners to find the challenges they face, the marketing strategies used, product innovations carried out, and the use of digital technology. The research concluded that MSME entrepreneurs are experiencing various challenges, including reduced demand due to changes in consumer tastes, difficulties in obtaining supplies of raw materials, limited digital marketing strategies, and intense competition with modern culinary types. Even so, the unique taste of traditional dishes is still loved, especially when it comes to special religious celebrations. The strategy includes improving product quality, various interesting innovations, as well as utilizing digital marketing via social media and attending culinary events. The results of this research show that to maintain the sustainability of traditional culinary MSMEs, good cooperation is needed between product innovation, application of technology, and support from the community and government.